Lanthanoid-doped quaternary garnets as phosphors for high brightness cathodoluminescence-based light sources. Issue 8 (August 2022) - Korjik, M.; Bondarau, A.; Dosovitskiy, G.; Dubov, V.; Gordienko, K.; Karpuk, P.; Komendo, I.; Kuznetsova, D.; Mechinsky, V.; Pustovarov, V.; Smyslova, V.; Tavrunov, D.; et al.
Abstract: Gadolinium-yttrium- aluminum-gallium garnets (GYAGG) doped and codoped with Eu, Tb, and Ce were manufactured as ceramics to develop long-wavelength phosphors for high-brightness white light sources based on cathodoluminescence (CL). The CL light yield (LY) of Tb-doped ceramics at high-intensity electron beam excitation is shown to be more than twice as high as that of the conventional phosphor YAG:Ce, whereas codoping with Eu to redshift the chromaticity results in reducing the LY approximately to the level of YAG:Ce. The LY might be substantially improved by using a mix of Tb- and Eu-doped GYGAG powders instead of a single codoped GYGAG to produce ceramic phosphor. The high LY is explained by favorable contribution of Gd sublattice in excitation transfer to activator ions. Chromaticity of phosphors GYGAG:Tb, Eu can be tuned in a wide range by varying the ratio of Tb to Eu concentration. They are radiation resistant and stabile in the temperature range from 300 to 450 K. Abstract : Cathodoluminescence; Light yield; Europium; Terbium; Chromaticity.